Implementation of the asset management system in PT. Bara Prima Utama - Asmara, Rina Yuliastuty; Kamil, Islamiah; Akbar, Muhammad Iqbal; Ariani, Meiliyah (Central Community Development Journal, 2024)
Effective asset management is a key factor for supporting the sustainability of mining company operations. This community benefits from the execution of the Resource Administration Framework at PT. Bara Prima Utama, which works within the coal mining division. This framework is planned to improve the proficiency of observing, upkeeping, and administering the company's settled resources to optimize resource utilization and decrease operational costs. Through the application of data innovation in resource information administration, a company can distinguish resource conditions in real time and make quicker and more exact vital choices. In expansion, preparation for asset administration staff is additionally carried out to guarantee the ability to work this unused system. This execution is anticipated to extend the efficiency and support of a company's operations and amplify the life of resources. This program also bolsters the company's commitment to a more proficient and dependable administration of assets.